Reading Vilna in the First World War - Weeks, Theodore R. (Colloquia, 2021)
The outbreak of war in August 1914 marked a new era in the history of Vilna for all of the city’s inhabitants, but perhaps for the Jews most of all. The world war accelerated the processes of political and economic modernisation, to the detriment of local Jews. These processes were not, however, immediately evident to local residents, though the more far-seeing among them feared for the worst. After all, when had Jews gained from military action? In this short paper, I will give an overview of the impact of the First World War on Vilna, and highlight two specific, very different, sources: Paul Monty’s Wanderstunden in Vilna, a guidebook for German soldiers, and Hirsz Abramowicz’s Profiles of a Lost World, a memoir published later (in Yiddish) by a long-time Vilna resident.